Effect of Auditor Professionalism, Experience, Accountability, Competence, and Independence on Audit QualityEffect of Auditor Professionalism, Experience, Accountability, Competence, and Independence on Audit Quality - Natalie, Joyce; Simorangkir, Enda Noviyanti; Tanaka, Viorencia; Hutagalung, Galumbang; Rajagukguk, Adi Putra (Akuntansi Prima, 2025)
The objective of this research is to identify the effect of Auditor Professionalism, Experience, Accountability, Competence, and Independence on Audit Quality within Public Accounting Firms (KAP) in Medan City.The study employs a quantitative approach and utilizes a sample of auditors working at KAP in Medan, selected using Nonprobability Sampling with a purposive sampling method through questionnaires.The research findings indicate that there is a partial significant effect of Professionalim, Experience, Accountability, Competence, and Independence on Audit Quality.Furthermore, simultaneously, Professionalism, Experience, Accountability, Competence, and Independence are proven to have a positive and significant effect on Audit Quality.